Iocasia fonsfrigidae NS-1 gen. nov., sp. nov., a Novel Deep-Sea Bacterium Possessing Diverse Carbohydrate Metabolic Pathways - Zhang, Jing; Zhang, Yuechao; Liu, Rui; Cai, Ruining; Liu, Fanghua; Sun, Chaomin (Frontiers in Microbiology, 2021)
Resolving metabolisms of deep-sea microorganisms is crucial for understanding ocean energy cycling. Here, a strictly anaerobic, Gram-negative strain NS-1 was isolated from the deep-sea cold seep in the South China Sea. Phylogenetic analysis based on 16S rRNA gene sequence indicated that strain NS-1 was most closely related to the type strain Halocella cellulosilytica DSM 7362T (with 92.52% similarity). In combination of phylogenetic, genomic and physiological traits with strain NS-1, it was proposed to be a representative of a novel genus in the family Halanaerobiaceae, for which Iocasia fonsfrigidae NS-1 was named. Of note, I. fonsfrigidae NS-1 could metabolize multiple carbohydrates including xylan, alginate, starch and lignin and thereby producing diverse fermentation products such as hydrogen, lactate, butyrate and ethanol. The expressions of key genes responsible for carbohydrates degradation as well as productions of above small molecular substrates when strain NS-1 cultured under different conditions, were further analyzed by transcriptomic methods. We thus predict part of the ecological role of Iocasia sp. is likely in the fermentation of products from the degradation of diverse carbohydrates to produce hydrogen as well as other small molecules, which in turn are utilized by other members of cold seep microbes.